The effects of the climate change and the drought stress on potato production – A review - Kávássy, Gergely; Szabó, András; Szabó, Éva (Acta Agraria Debreceniensis, 2025)
Potato (Solanum tuberosum) is the fifth most important cultivated crop according to its growing area and fourth by its production volume. Originated from the Andes of South America throughout the last five centuries spread over the world and became a global staple food. Over the years potato production has greatly evolved due to advancement in agrotechnology reflecting in higher yields contrary to the worldwide decreasing production area. The wide range of potato’s ability for adaptation allows it to thrive in many different soil types and climates making it a main contributor in food security. Nonetheless rising temperatures, extreme weather events, water scarcity driven by climate change imposes serious challenges and threats for global potato production. This review presents the short history of potato cultivation, statistics of present and past production and agroecological needs for ideal farming. The review also attempts to explore the impact of climate change on potato growing spotlighting on drought and heat sensitivity. To deal with these climate change induced challenges several mitigation options are proposed just as foliar applications of salicylic acid, hydrogen peroxide, silicon and micronutrients to elevate perseverance against abiotic stresses.